PEMANFAATAN KOLAM TANAH DI LAHAN RAWA UNTUK PEMBESARAN IKAN GABUS DI SMK NEGERI 1 OGAN ILIR - Rahma Mulyani; Sumantriyadi Sumantriyadi; Lia Perwita Sari; Sujaka Nugraha; Santi Mayasari; Humairani Humairani (Jurnal Abdi Insani, 2023)
In Indonesia, the potential for snakehead fish is very high, especially in South Sumatra. Swamps Areas in Indonesia have great potential to be developed as land used for the fisheries sector. Snakehead fish can be cultivated in swamp waters. The purpose of this PKM activity is expected to be able to provide education and information for teachers and students about how to use swamp land as a place for snakehead fish cultivation. The method used is the observation and preparation stage, the coordination stage, the tool and material preparation stage, and the final stage of implementing PKM activities. The target of the results of Community Service Program activities that have been carried out in general are the community that is specifically aimed at students and teachers at SMK Negeri 1 Inderalaya Selatan, Ogan Ilir Regency, which has specifically been attended by 60 people. During the implementation of this PKM activity, the activity was carried out in 3 major activities, the first was a speech from the principal of SMK N 1 Ogan Ilir and continued by the PKL Team Leader, the second session was followed by a presentation session of 6 materials and the last was a demonstration or practical activity. measuring the quality of swamp water in the school environment as well as socializing fish farming study programs. The results of this PKM are used to increase student interest and knowledge to find out more about the use of swamp land which is often neglected in the area and of course can provide an introduction to fish farming study programs as a place to explore knowledge and abilities to enrich insights about fish farming. From the results of this PKM activity, as many as 60 participants who had been given education about the use of swamp land for snakehead fish cultivation showed an increased understanding of the material provided compared to before the education.